2018
DOI: 10.1002/pon.4773
|View full text |Cite
|
Sign up to set email alerts
|

Facing death alone or together? Investigating the interdependence of death anxiety, dysfunctional attitudes, and quality of life in patient‐caregiver dyads confronting lung cancer

Abstract: Death anxiety influences dysfunctional attitudes and quality of life of both patients and caregivers. Our results support the relevance of dysfunctional attitudes in understanding the impact of death anxiety and underscore the need for parallel psychosocial interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies reported on relatives of advanced cancer patient’s [9,10,11,13,15,16,17,18,19,20,21,22,23,24,26,27,28,29,30,31,32,34,36,37,38,39,42,43,44,46,47,48,49,50,51,52,53,55,56,57,58,59,60,61,65,66,67] and 15 studies included relatives of mixed patient samples [12,14,25,33,35,40,41,45,54,62,63,64,68,69,70]. The environment in which the patient received palliative or hospice care were home care in 18 studies [10,14,25,26,27,30,3...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations